Preparation method of piezoelectric flexible super-hydrophobic raindrop sensor
By combining the superhydrophobic surface with the piezoelectric raindrop sensor, a flexible superhydrophobic raindrop sensor was prepared, which solved the performance decay of raindrop sensors in the prior art in heavy rain and extreme environments, and achieved higher measurement accuracy and environmental adaptability.
Patent Information
- Application Number
- CN202411507683.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-28
AI Technical Summary
The existing piezoelectric raindrop sensors have deteriorated performance due to raindrop deposition in heavy rain environments and cannot work properly in extreme environments, with reduced measurement accuracy and limited response thresholds.
Using the preparation method of a piezoelectric flexible superhydrophobic raindrop sensor, the superhydrophobic surface is combined with a piezoelectric raindrop sensor, and a sensor film with superhydrophobic properties and high voltage electrical properties is prepared by combining modified barium titanate BTO powder and polydimethylsiloxane PDMS.
The detection frequency and rainfall intensity threshold of raindrops are improved, and the residual droplets on the surface of the sensor and the freezing in extreme environments are prevented, the service life of the sensor is extended, and the measurement accuracy and environmental adaptability are improved.
Smart Images

Figure CN119546164A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a sensor, and in particular to a method for preparing a piezoelectric flexible super-hydrophobic raindrop sensor. Background Art
[0002] Rainfall information detection has become an important part of routine meteorological observation and meteorological-related industries, and is of great significance to weather forecasting, flood control, agricultural planting, transportation planning, etc. Piezoelectric raindrop sensors have stood out among many raindrop sensors due to their large range, high measurement accuracy, and low power consumption. However, like other types of rain sensors, existing piezoelectric raindrop sensors will experience performance degradation due to raindrop deposition in heavy rain environments, such as decreased measurement accuracy; in addition, current piezoelectric raindrop sensors also have defects such as limited threshold response to rainfall intensity and inability to work normally in extreme environments such as low temperature and freezing rain. Summary of the invention
[0003] In order to solve the problems existing in the background technology, the present invention provides a method for preparing a piezoelectric flexible super-hydrophobic raindrop sensor. The piezoelectric flexible super-hydrophobic raindrop sensor of the present invention combines a super-hydrophobic surface with a piezoelectric raindrop sensor, which can improve the detection frequency of raindrops and the rainfall intensity threshold, effectively prevent droplet residue on the sensor surface and freezing in extremely cold environments, improve the sensor's sensing performance and service life, and can also reduce the impact of ambient humidity and droplet surface deposition on the sensing performance, thereby improving the sensor's measurement accuracy and environmental adaptability.
[0004] The technical solution adopted by the present invention is:
[0005] 1. A method for preparing a piezoelectric flexible super-hydrophobic raindrop sensor, comprising:
[0006] Step 1: Dissolve polyvinylidene fluoride-trifluoroethylene P (VDF-TrFE) powder (Polyvinylidene Fluoride-Trifluoroethylene) in dimethylformamide DMF (N,N-Dimethylformamide), and stir evenly at room temperature to obtain a first mixed solution; dissolve barium titanate BTO nanoparticles (BaTiO3) in a hydrogen peroxide solution, and mix evenly after ultrasonic treatment to obtain a second mixed solution, pour the second mixed solution into a culture dish and place it in an oven for curing to obtain modified barium titanate BTO powder.
[0007] Step 2: Dissolve the modified barium titanate BTO powder in the first mixed solution, and perform ultrasonic treatment to mix evenly to obtain a third mixed solution, pour the third mixed solution into a culture dish and place it in an oven to solidify and form an initial film.
[0008] Step 3: The initial film is annealed to obtain a BTO / P (VDF-TrFE) film, and then the electrode material is deposited in the form of a film on the surface of the BTO / P (VDF-TrFE) film and connected with a wire to obtain a piezoelectric composite film.
[0009] Step 4: Pour the polydimethylsiloxane PDMS solution into the copper template with the microstructure and distribute it evenly. Put the copper template into a culture dish and place it in an oven for semi-curing, then take out the copper template.
[0010] Step 5: Cover one side of the piezoelectric composite film on the semi-cured polydimethylsiloxane (PDMS) on the copper template, and spin-coat the other side of the piezoelectric composite film with a polydimethylsiloxane (PDMS) solution for encapsulation. Place the copper template in a culture dish and place it in an oven for curing and then take out the copper template. Use tweezers to remove the cured piezoelectric composite-superhydrophobic film on the copper template and place it on a glass slide.
[0011] Step 6: Spin-coat the surface of the piezoelectric composite-super-hydrophobic film adhered to the glass slide with the modified nano-titanium dioxide spin-coating liquid, and place it in an oven for curing. Repeat step 6 5-6 times to prepare a piezoelectric flexible super-hydrophobic raindrop sensor.
[0012] The wire of the piezoelectric flexible super-hydrophobic raindrop sensor is connected to a data collector, and the voltage signal fluctuation of the piezoelectric sensor can be obtained by collecting signals through the sensor to detect raindrops. The present invention uses a super-hydrophobic + piezoelectric sensor to produce a super-hydrophobic piezoelectric sensor for detecting raindrops.
[0013] In the step 1, the molar ratios of vinylidene fluoride VDF and trifluoroethylene TrFE in the polyvinylidene fluoride-trifluoroethylene P (VDF-TrFE) powder are 55% and 45% respectively; polyvinylidene fluoride-trifluoroethylene P (VDF-TrFE) powder and dimethylformamide DMF in a mass ratio of 1:10 are mixed at room temperature and magnetically stirred to obtain a first mixed solution.
[0014] In the step 1, barium titanate (BTO) nanoparticles with a particle size of 100 nm are dissolved in a hydrogen peroxide solution with a mass fraction of 35 wt% at a ratio of 0.2 g / mL and placed in a centrifuge tube. The centrifuge tube is placed in an ultrasonic cleaner at 50°C for ultrasonic treatment and water bath mixing and cleaning for 1 hour to obtain a uniform second mixed solution. The second mixed solution is poured into a culture dish and placed in an oven at 70°C for curing and molding to obtain modified barium titanate (BTO) powder.
[0015] In the step 2, the modified barium titanate BTO powder is dissolved in the first mixed solution at a mass ratio of 30% and placed in a centrifuge tube. The centrifuge tube is placed in an ultrasonic cleaner at 50°C for ultrasonic treatment and water bath mixing and cleaning for 2 hours to obtain a uniform third mixed solution. The third mixed solution is poured into a culture dish and the thickness of the third mixed solution is leveled with a spatula, and then placed in an oven at 80°C for curing to obtain an initial film.
[0016] In the step 3, the initial film is annealed at 120° C. for 90 minutes to eliminate residual stress, refine grains and improve crystallinity, thereby obtaining a 25-32 μm BTO / P (VDF-TrFE) film.
[0017] In the step 3, under vacuum conditions, the four sides of the BTO / P (VDF-TrFE) film are first covered with a mask to prevent short circuit caused by conduction; then a gold target is used as an electrode material, and the magnetron sputtering power of the magnetron sputtering instrument is set to 80W. After the gold target is sputtered for 10 minutes by the magnetron sputtering instrument, two layers of 50nm gold electrodes are deposited in the form of thin films on the two side surfaces of the BTO / P (VDF-TrFE) film. The two side surfaces are sputtered for 5 minutes respectively, and the two layers of gold electrodes are used as upper and lower poles respectively; then the BTO / P (VDF-TrFE) film is polarized by a high-voltage electric field that increases by 0.6kV every 5 minutes and increases to 3kV, so that the BTO / P (VDF-TrFE) film has a higher β-phase content and a regular orientation, thereby improving the piezoelectric properties of the BTO / P (VDF-TrFE) film; finally, the upper and lower poles of the BTO / P (VDF-TrFE) film are connected to the copper wire through a conductive silver paste to obtain a piezoelectric composite film.
[0018] In the step 4, the microstructure in the copper template is a truncated cone micro-column structure evenly spaced in an array; a polydimethylsiloxane (PDMS) solution is poured into the copper template with the microstructure and evenly distributed, the copper template is placed in a culture dish and placed in an oven for semi-curing at 80°C, and then the copper template is taken out, and the semi-cured polydimethylsiloxane (PDMS) on the copper template is a sheet structure with a truncated cone micro-column structure evenly spaced in an array on one side.
[0019] In the step 5, the area of the piezoelectric composite film is smaller than the area of the semi-cured polydimethylsiloxane (PDMS) on the copper template, and the semi-cured polydimethylsiloxane (PDMS) has a microstructure on one side surface. After covering, the side surface of the piezoelectric composite film is located at the center position of the other side surface of the semi-cured polydimethylsiloxane (PDMS); the area of the polydimethylsiloxane (PDMS) spin-coated on the other side of the piezoelectric composite film using a spin coater is larger than the area of the piezoelectric composite film; the copper template is placed in a culture dish and placed in an oven to cure at 80°C, and then the copper template is taken out.
[0020] In the step 6, the preparation process of the modified nano titanium dioxide spin coating liquid is as follows: first, titanium dioxide particles with a particle size of 20 nm and anhydrous ethanol are added to a centrifuge tube at a ratio of 0.01 g / mL, and a micro-oscillator is used to oscillate for 10 minutes, and then placed in an ultrasonic cleaning machine at 50°C for ultrasonic treatment and water bath mixing and cleaning for 0.5 hours to obtain a uniform fourth mixed solution; using a pipette to draw octadecyl trimethoxysilane TMOS (trimethoxyoctadecylsilane) solution and drip it into the fourth mixed solution, and the centrifuge tube is placed in an ultrasonic cleaning machine at 50°C again for ultrasonic treatment and water bath mixing and cleaning for 1 hour, and then allowed to stand for 10 minutes to obtain a uniform modified nano titanium dioxide spin coating liquid, wherein the volume ratio of the octadecyl trimethoxysilane TMOS solution to the anhydrous ethanol is 1:100; the surface of the piezoelectric composite-superhydrophobic film is spin-coated with the modified nano titanium dioxide spin coating liquid and then placed in an oven for curing at 80°C.
[0021] 2. A piezoelectric flexible super-hydrophobic raindrop sensor:
[0022] The piezoelectric flexible super-hydrophobic raindrop sensor is prepared by the method described above.
[0023] The beneficial effects of the present invention are:
[0024] 1) The present invention aims at the problem that the piezoelectric signal generated when the raindrop particle size is extremely small is extremely weak, and the sensor itself has certain disturbances during the measurement process due to the influence of surrounding environmental factors. The rationality of the voltage acquisition value is specifically distinguished, the voltage peak range is set, and the detection accuracy is enhanced under the action of the filtering circuit.
[0025] 2) The present invention builds a simulated rainfall platform in the laboratory, and integrates multiple modules into a printed circuit board PCB (Printed Circuit Board) through hardware selection, which can realize signal collection when multiple droplets impact at different frequencies and different droplet volumes. Compared with the measurement results of a commercial tipping bucket rain sensor, the measurement error of the piezoelectric flexible super-hydrophobic raindrop sensor is only 1.6%, and it has better instantaneous performance.
[0026] 3) The present invention addresses the problems that during the droplet impact process, droplets are prone to residual liquid film forming, and when the impact frequency is high, the droplets are broken and pinned on the sensor surface. In addition, when the ambient temperature is low and has a certain humidity, droplets impacting the sensor surface will cause freezing rain and freeze, which will affect the sensor accuracy. The flexible super-hydrophobic piezoelectric composite film designed for this purpose allows the droplets to quickly detach from the film surface in a very short time. The detachment time is greater than the droplet dripping time interval, resulting in no droplet accumulation and adhesion, and has excellent anti-icing performance.
[0027] The present invention improves the existing piezoelectric raindrop sensor and develops a piezoelectric flexible super-hydrophobic raindrop sensor. In combination with a flexible super-hydrophobic surface, the contact bouncing behavior of raindrops on super-hydrophobic surfaces at different inclination angles is studied, and the optimal super-hydrophobic surface inclination angle is determined, which significantly shortens the droplet contact time and ensures that the droplets are completely separated from the sensor surface. The present invention can increase the detection frequency of raindrops and the rainfall intensity threshold, effectively prevent droplet residues on the sensor surface and freezing in extremely cold environments, improve the sensor's sensing performance and service life, and can also reduce the impact of environmental humidity and droplet surface deposition on the sensing performance, and improve the sensor's measurement accuracy and environmental adaptability. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The present invention is a flow chart for preparing a piezoelectric flexible super-hydrophobic raindrop sensor;
[0029] Figure 2 is a schematic diagram of a superhydrophobic truncated cone, where: Figure 2 (a) is a schematic diagram of the super-hydrophobic truncated cone array surface. Figure 2 (b) is a schematic diagram of the truncated cone array structure;
[0030] Figure 3 This is a physical picture of the flexible super-hydrophobic piezoelectric composite film;
[0031] Figure 4 Schematic diagram of multi-channel piezoelectric output when multiple droplets impact at different droplet sizes. DETAILED DESCRIPTION
[0032] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0033] The specific embodiments of the present invention are as follows:
[0034] Embodiment 1:
[0035] like Figure 1As shown, first, 5g of polyvinylidene fluoride-trifluoroethylene P (VDF-TrFE) powder is dissolved in 50g of dimethylformamide DMF, and stirred at room temperature to obtain a first mixed solution, wherein the molar ratios of polyvinylidene fluoride VDF and trifluoroethylene TrFE in the polyvinylidene fluoride-trifluoroethylene P (VDF-TrFE) powder are 55% and 45%, respectively. Then, 20g of barium titanate BTO nanoparticles with a particle size of 100nm are dissolved in 100ml of a 35wt% hydrogen peroxide solution, and placed in a centrifuge tube, and the centrifuge tube is placed in an ultrasonic cleaning machine at 50°C for ultrasonic treatment and water bath mixing and cleaning for 1h to obtain a uniform second mixed solution, and the second mixed solution is poured into a culture dish and placed in an oven at 70°C for curing and molding to obtain modified barium titanate BTO powder.
[0036] 15 g of modified barium titanate BTO powder was dissolved in 35 g of the first mixed solution and placed in a centrifuge tube. The centrifuge tube was placed in an ultrasonic cleaner at 50°C for ultrasonic treatment and water bath mixing and cleaning for 2 hours to obtain a uniform third mixed solution. The third mixed solution was poured into a culture dish and the thickness of the third mixed solution was leveled with a spatula, and then placed in an oven at 80°C for curing to obtain an initial film.
[0037] The initial film was annealed at 120°C for 90 minutes to eliminate residual stress, refine grains and improve crystallinity, and a 28 μm BTO / P (VDF-TrFE) film was obtained; then a gold target was used for thin film deposition as follows:
[0038] Under vacuum conditions, the four sides of the BTO / P (VDF-TrFE) film are first covered with a mask to prevent short circuit caused by conduction; the magnetron sputtering power of the magnetron sputtering instrument is set to 80W, and the gold target is sputtered by the magnetron sputtering instrument for 10 minutes, and then two layers of 50nm gold electrodes are deposited in the form of thin films on the two sides of the BTO / P (VDF-TrFE) film. The two sides are sputtered for 5 minutes respectively, and the two layers of gold electrodes serve as upper and lower poles respectively; then the BTO / P (VDF-TrFE) film is polarized by a high-voltage electric field that increases by 0.6kV every 5 minutes and rises to 3kV, so that the BTO / P (VDF-TrFE) film has a higher β-phase content and a regular orientation, thereby improving the piezoelectric properties of the BTO / P (VDF-TrFE) film; finally, the upper and lower poles of the BTO / P (VDF-TrFE) film are connected to the copper wire through conductive silver paste to obtain a piezoelectric composite film.
[0039] BTO / P (VDF-TrFE) film has polymers with various crystalline forms (also called crystal phases), mainly including α, β, γ, δ and ε phases. The β phase has excellent electrical properties and can retain a high polarization strength after the external electric field is removed, so high voltage electric field polarization is used for strengthening. Finally, through quasi-static d 33 The tester measured the piezoelectric composite film d 33 The piezoelectric coefficient in the direction is d 33 =38.0pc·N -1 .d 33 The coefficient represents the rate of change of charge density generated by stress perpendicular to the polarization direction of the piezoelectric material. It is one of the important parameters to measure the performance of piezoelectric materials.
[0040] The polydimethylsiloxane PDMS solution is poured into the copper template with microstructures and evenly distributed. The microstructure in the copper template is a truncated cone micro-column structure with evenly spaced arrays, such as Figure 2 (a) and Figure 2 As shown in (b), where D p and D v are the top and bottom diameters of the truncated cone microcolumn, S p is the distance between the bottoms of two adjacent truncated cone microcolumns, H is the height of the truncated cone microcolumn; α is the half apex angle of the truncated cone microcolumn, and T is the substrate thickness of the semi-cured polydimethylsiloxane PDMS.
[0041] The copper template was then placed in a culture dish and placed in an oven for semi-curing at 80°C. The copper template was then taken out. The semi-cured polydimethylsiloxane (PDMS) on the copper template was a sheet-like structure with an array of evenly spaced truncated cone micro-pillar structures on one side. p =10μm, D v =100μm, S p =50μm, H=400μm, α=10°, T=100μm.
[0042] One side of the piezoelectric composite film is covered on the semi-cured polydimethylsiloxane (PDMS) on the copper template, and the polydimethylsiloxane (PDMS) solution is spin-coated on the other side of the piezoelectric composite film for packaging, the area of the piezoelectric composite film is smaller than the area of the semi-cured polydimethylsiloxane (PDMS) on the copper template, one side of the semi-cured polydimethylsiloxane (PDMS) has a microstructure, and after covering, one side of the piezoelectric composite film is located at the center of the other side of the semi-cured polydimethylsiloxane (PDMS); the area of the polydimethylsiloxane (PDMS) spin-coated on the other side of the piezoelectric composite film using a uniform glue spin coater is larger than the area of the piezoelectric composite film; the copper template is placed in a culture dish and placed in an oven for curing at 80°C, and then the copper template is taken out, the cured piezoelectric composite-superhydrophobic film on the copper template is removed with tweezers, and then placed on a glass slide.
[0043] Then, the surface of the piezoelectric composite-super-hydrophobic film adhered to the glass slide was spin-coated with the modified nano-titanium dioxide spin-coating liquid, and placed in an oven to solidify at 80°C. After repeating step 6 for 6 times, a piezoelectric flexible super-hydrophobic raindrop sensor was prepared. Figure 3 As shown, the piezoelectric flexible super-hydrophobic raindrop sensor is designed by combining the excellent water repellency and shorter droplet contact time of the flexible super-hydrophobic surface of the truncated cone square array structure.
[0044] The preparation process of the modified nano-titanium dioxide spin-coating liquid is as follows: first, 0.6 g of titanium dioxide particles with a particle size of 20 nm and 60 ml of anhydrous ethanol are added to a centrifuge tube and mixed, and a micro-oscillator is used to oscillate for 10 minutes, and then the mixture is placed in an ultrasonic cleaner at 50°C for ultrasonic treatment and water bath mixing and cleaning for 0.5 hours to obtain a uniform fourth mixed solution; 600 μl of octadecyltrimethoxysilane TMOS solution is drawn with a pipette and dripped into the fourth mixed solution, and the centrifuge tube is placed in an ultrasonic cleaner at 50°C again for ultrasonic treatment and water bath mixing and cleaning for 1 hour, and then allowed to stand for 10 minutes to obtain a uniform modified nano-titanium dioxide spin-coating liquid; the surface of the piezoelectric composite-super-hydrophobic film is spin-coated with the modified nano-titanium dioxide spin-coating liquid and then placed in an oven for curing at 80°C.
[0045] The piezoelectric flexible super-hydrophobic raindrop sensor prepared in Example 1 is used for signal acquisition. First, the piezoelectric output signal is acquired based on the simulated rainfall signal acquisition platform constructed in the laboratory. The acquisition method refers to the real-time acquisition of rainfall information through the synergy of software and hardware. The acquisition system is integrated, and the real-time and rapid response of the piezoelectric signal when the raindrop hits is realized through the main control chip, the switch chip, and the signal acquisition conversion module, and the calculation and display of the accumulated rainfall are completed. Figure 4As shown in the figure, the difference in the order of droplets falling during the transportation process will lead to inconsistent initial points of the signal. When multiple droplets fall, the average peak values of the four-channel piezoelectric output are 60mV, 74mV, 90mV, and 111mV respectively. The piezoelectric sensor cannot produce a theoretical response to the raindrop pulse force in the actual structure, resulting in a large difference between the upper and lower peak values of a single signal. The collapse of the air cavity and the convergence of the capillary wave produce the Worthington effect. Due to the conservation of momentum, a jet will be generated inside the droplet in the opposite direction. The surface of the flexible super-hydrophobic raindrop sensor is subjected to the secondary downward force of the droplet, resulting in the appearance of the second peak.
[0046] Then, data preprocessing is performed. The actual collected signals are affected by various factors such as electromagnetic interference, mechanical vibration, and power supply stability. In order to extract key information and reduce errors, the data needs to be denoised. In this embodiment, the droplets drip onto the sensor surface through the simulated rainfall platform to generate a charge signal corresponding to the impact force. After circuit conversion, the weak charge signal is converted into an easily measurable piezoelectric signal, and the rationality of the voltage collection value is specifically distinguished, such as Figure 4 As shown, the voltage acquisition values are respectively divided into -25~100mV and 58~63mV, -25~125mV and 72~75mV, -25~150mV and 85~95mV, -25~200mV and 107~115mV. The voltage peak range is set, and the detection accuracy is enhanced under the action of the filtering circuit. After normalization, the voltage signal is amplified and filtered.
[0047] Then the data set is annotated and constructed. The flexible super-hydrophobic raindrop sensor obtains the calibrated raindrop particle size by extracting the peak value of the piezoelectric signal of the raindrop. The number of peak values of the pulse piezoelectric signal is the number of raindrops, and the total rainfall is accumulated. The adaptive correction coefficients α (36.05-82.33) and β (0.79-0.82) under the current rainfall intensity are iterated by the gradient descent method. The adaptive correction coefficient α under different rainfall intensities changes accordingly. Therefore, the voltage signal of the piezoelectric flexible super-hydrophobic raindrop sensor is accumulated to represent the rainfall intensity. After the AD analog-to-digital conversion to the digital signal, the signal is amplified and the signal of the piezoelectric sensor is analyzed from the time domain perspective. The time domain analysis can realize the real-time change of the piezoelectric signal generated when the raindrop hits the sensor surface with time as the coordinate axis and observe the peak value and uniformity of the piezoelectric signal. After the peak signal detection and screening, the data is cached into the cache area for peak extraction, and the collected peak voltage is converted into ASCII code and output bit by bit to the host computer software end, and the rainfall per unit time is accumulated in real time. The measurement result of the sensor of the present invention compared with that of a commercial tipping bucket rain sensor shows that the measurement error of the piezoelectric flexible super-hydrophobic raindrop sensor is only 1.6%, and the sensor has better instantaneous performance.
[0048] The present invention also studies the contact bouncing behavior of raindrops on super-hydrophobic surfaces at different tilt angles, and determines the optimal tilt angle of the super-hydrophobic surface. When the tilt angle α is 10°, the Weber number We n =39.5, the contact time of the droplet is only 2.6ms, which is about 85% shorter than the theoretical contact time of 17ms. Therefore, the tilt angle here is α=10°. It can be seen that the present invention significantly shortens the contact time of the droplet and ensures that the droplet is completely separated from the sensor surface.
[0049] Embodiment 2:
[0050] First, 10g of polyvinylidene fluoride-trifluoroethylene P (VDF-TrFE) powder was dissolved in 100g of dimethylformamide DMF, and stirred at room temperature to obtain a first mixed solution, wherein the molar ratios of polyvinylidene fluoride VDF and trifluoroethylene TrFE in the polyvinylidene fluoride-trifluoroethylene P (VDF-TrFE) powder were 55% and 45%, respectively. Then, 30g of barium titanate BTO nanoparticles with a particle size of 100nm were dissolved in 150ml of a 35wt% hydrogen peroxide solution, and placed in a centrifuge tube, and the centrifuge tube was placed in an ultrasonic cleaning machine at 50°C for ultrasonic treatment and water bath mixing and cleaning for 1h to obtain a uniform second mixed solution, and the second mixed solution was poured into a culture dish and placed in an oven at 70°C for curing and molding to obtain modified barium titanate BTO powder.
[0051] 30 g of modified barium titanate BTO powder was dissolved in 70 g of the first mixed solution and placed in a centrifuge tube. The centrifuge tube was placed in an ultrasonic cleaner at 50°C for ultrasonic treatment and water bath mixing and cleaning for 2 hours to obtain a uniform third mixed solution. The third mixed solution was poured into a culture dish and the thickness of the third mixed solution was leveled with a spatula, and then placed in an oven at 80°C for curing to obtain an initial film.
[0052] The initial film was annealed at 120°C for 90 minutes to eliminate residual stress, refine grains and improve crystallinity, and a 30 μm BTO / P (VDF-TrFE) film was obtained; then a gold target was used for thin film deposition as follows:
[0053] Under vacuum conditions, the four sides of the BTO / P (VDF-TrFE) film are first covered with a mask to prevent short circuit caused by conduction; the magnetron sputtering power of the magnetron sputtering instrument is set to 80W, and the gold target is sputtered by the magnetron sputtering instrument for 10 minutes, and then two layers of 50nm gold electrodes are deposited in the form of thin films on the two sides of the BTO / P (VDF-TrFE) film. The two sides are sputtered for 5 minutes respectively, and the two layers of gold electrodes serve as upper and lower poles respectively; then the BTO / P (VDF-TrFE) film is polarized by a high-voltage electric field that increases by 0.6kV every 5 minutes and rises to 3kV, so that the BTO / P (VDF-TrFE) film has a higher β-phase content and a regular orientation, thereby improving the piezoelectric properties of the BTO / P (VDF-TrFE) film; finally, the upper and lower poles of the BTO / P (VDF-TrFE) film are connected to the copper wire through conductive silver paste to obtain a piezoelectric composite film.
[0054] The polydimethylsiloxane (PDMS) solution is poured into a copper template with a microstructure and distributed evenly. The microstructure in the copper template is a truncated cone micro-column structure with an array evenly spaced distribution. The copper template is then placed in a culture dish and placed in an oven for semi-curing at 80°C. The copper template is then taken out. The semi-cured polydimethylsiloxane (PDMS) on the copper template is a sheet structure with a truncated cone micro-column structure with an array evenly spaced distribution on one side.
[0055] One side of the piezoelectric composite film is covered on the semi-cured polydimethylsiloxane (PDMS) on the copper template, and the polydimethylsiloxane (PDMS) solution is spin-coated on the other side of the piezoelectric composite film for packaging, the area of the piezoelectric composite film is smaller than the area of the semi-cured polydimethylsiloxane (PDMS) on the copper template, one side of the semi-cured polydimethylsiloxane (PDMS) has a microstructure, and after covering, one side of the piezoelectric composite film is located at the center of the other side of the semi-cured polydimethylsiloxane (PDMS); the area of the polydimethylsiloxane (PDMS) spin-coated on the other side of the piezoelectric composite film using a uniform glue spin coater is larger than the area of the piezoelectric composite film; the copper template is placed in a culture dish and placed in an oven for curing at 80°C, and then the copper template is taken out, the cured piezoelectric composite-superhydrophobic film on the copper template is removed with tweezers, and then placed on a glass slide.
[0056] Then, the surface of the piezoelectric composite-super-hydrophobic film adhered to the glass slide was spin-coated with the modified nano-titanium dioxide spin-coating liquid, and placed in an oven to solidify at 80°C. After repeating step 6 for 6 times, a piezoelectric flexible super-hydrophobic raindrop sensor was prepared. Figure 3 As shown, the piezoelectric flexible super-hydrophobic raindrop sensor is designed by combining the excellent water repellency and shorter droplet contact time of the flexible super-hydrophobic surface of the truncated cone square array structure.
[0057] The preparation process of the modified nano-titanium dioxide spin-coating liquid is as follows: first, 0.8 g of titanium dioxide particles with a particle size of 20 nm and 80 ml of anhydrous ethanol are added to a centrifuge tube and mixed, and a micro-oscillator is used to oscillate for 10 minutes, and then the mixture is placed in an ultrasonic cleaner at 50°C for ultrasonic treatment and water bath mixing and cleaning for 0.5 hours to obtain a uniform fourth mixed solution; 800 μl of octadecyltrimethoxysilane TMOS solution is drawn with a pipette and dripped into the fourth mixed solution, and the centrifuge tube is placed in an ultrasonic cleaner at 50°C again for ultrasonic treatment and water bath mixing and cleaning for 1 hour, and then allowed to stand for 10 minutes to obtain a uniform modified nano-titanium dioxide spin-coating liquid; the surface of the piezoelectric composite-super-hydrophobic film is spin-coated with the modified nano-titanium dioxide spin-coating liquid and then placed in an oven for curing at 80°C.
[0058] The wire of the piezoelectric flexible super-hydrophobic raindrop sensor is connected to a data collector, and the voltage signal fluctuation of the piezoelectric sensor can be obtained by collecting signals through the sensor to detect raindrops. The present invention uses a super-hydrophobic + piezoelectric sensor to produce a super-hydrophobic piezoelectric sensor for detecting raindrops.
[0059] The above description is only a preferred embodiment of the present invention and is not intended to be limiting thereof. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a piezoelectric flexible super-hydrophobic raindrop sensor, characterized in that: include: Step 1: dissolving polyvinylidene fluoride-trifluoroethylene P(VDF-TrFE) powder in dimethylformamide DMF, and stirring at room temperature to obtain a first mixed solution; dissolving barium titanate BTO nanoparticles in a hydrogen peroxide solution, and performing ultrasonic treatment to mix evenly to obtain a second mixed solution, and pouring the second mixed solution into a culture dish and placing it in an oven to solidify and shape to obtain modified barium titanate BTO powder; Step 2: dissolving the modified barium titanate BTO powder in the first mixed solution, and performing ultrasonic treatment to mix the mixture evenly to obtain a third mixed solution, pouring the third mixed solution into a culture dish and placing the mixture in an oven to solidify and form an initial film; Step 3: annealing the initial film to obtain a BTO / P (VDF-TrFE) film, and then depositing the electrode material in the form of a film on the surface of the BTO / P (VDF-TrFE) film and connecting the wires to obtain a piezoelectric composite film; Step 4: Pour the polydimethylsiloxane (PDMS) solution into the copper template with the microstructure and distribute it evenly, put the copper template into a culture dish and place it in an oven for semi-curing, then take out the copper template; Step 5: Cover one side of the piezoelectric composite film on the semi-cured polydimethylsiloxane PDMS on the copper template, and spin-coat the polydimethylsiloxane PDMS solution on the other side of the piezoelectric composite film for packaging, put the copper template into a culture dish and place it in an oven for curing, then take out the copper template, and remove the cured piezoelectric composite-superhydrophobic film on the copper template; Step 6: Spin-coat the surface of the piezoelectric composite-super-hydrophobic film with the modified nano-titanium dioxide spin-coating liquid, and place it in an oven for curing and forming. Repeat step 6 5-6 times to prepare a piezoelectric flexible super-hydrophobic raindrop sensor.
2. The method for preparing the piezoelectric flexible super-hydrophobic raindrop sensor according to claim 1, characterized in that: In the step 1, the molar ratios of vinylidene fluoride VDF and trifluoroethylene TrFE in the polyvinylidene fluoride-trifluoroethylene P (VDF-TrFE) powder are 55% and 45% respectively; polyvinylidene fluoride-trifluoroethylene P (VDF-TrFE) powder and dimethylformamide DMF in a mass ratio of 1:10 are mixed at room temperature and magnetically stirred to obtain a first mixed solution.
3. The method for preparing the piezoelectric flexible super-hydrophobic raindrop sensor according to claim 1, characterized in that: In the step 1, barium titanate (BTO) nanoparticles with a particle size of 100 nm are dissolved in a hydrogen peroxide solution with a mass fraction of 35 wt% at a ratio of 0.2 g / mL and placed in a centrifuge tube. The centrifuge tube is placed in an ultrasonic cleaner at 50°C for ultrasonic treatment and water bath mixing and cleaning for 1 hour to obtain a uniform second mixed solution. The second mixed solution is poured into a culture dish and placed in an oven at 70°C for curing and molding to obtain modified barium titanate (BTO) powder.
4. The method for preparing the piezoelectric flexible super-hydrophobic raindrop sensor according to claim 1, characterized in that: In the step 2, the modified barium titanate BTO powder is dissolved in the first mixed solution at a mass ratio of 30% and placed in a centrifuge tube. The centrifuge tube is placed in an ultrasonic cleaner at 50°C for ultrasonic treatment and water bath mixing and cleaning for 2 hours to obtain a uniform third mixed solution. The third mixed solution is poured into a culture dish and the thickness of the third mixed solution is leveled with a spatula, and then placed in an oven at 80°C for curing to obtain an initial film.
5. The method for preparing the piezoelectric flexible super-hydrophobic raindrop sensor according to claim 1, characterized in that: In the step 3, the initial film is annealed at 120° C. for 90 minutes to obtain a 25-32 μm BTO / P (VDF-TrFE) film.
6. The method for preparing the piezoelectric flexible super-hydrophobic raindrop sensor according to claim 1, characterized in that: In the step 3, under vacuum conditions, firstly, the four sides of the BTO / P (VDF-TrFE) film are covered with a mask, and then a gold target is used as an electrode material, and the magnetron sputtering power of the magnetron sputtering instrument is set to 80W. After the gold target is sputtered for 10 minutes by the magnetron sputtering instrument, two layers of 50nm gold electrodes are deposited in the form of thin films on the two sides of the BTO / P (VDF-TrFE) film, and the two layers of gold electrodes serve as upper and lower poles respectively; then, the BTO / P (VDF-TrFE) film is polarized by a high-voltage electric field that increases by 0.6kV every 5 minutes until it increases to 3kV; finally, the upper and lower poles of the BTO / P (VDF-TrFE) film are connected to the copper wire through conductive silver paste to prepare a piezoelectric composite film.
7. The method for preparing the piezoelectric flexible super-hydrophobic raindrop sensor according to claim 1, characterized in that: In the step 4, the microstructure in the copper template is a truncated cone micro-column structure evenly spaced in an array; a polydimethylsiloxane (PDMS) solution is poured into the copper template with the microstructure and evenly distributed, the copper template is placed in a culture dish and placed in an oven for semi-curing at 80°C, and then the copper template is taken out, and the semi-cured polydimethylsiloxane (PDMS) on the copper template is a sheet structure with a truncated cone micro-column structure evenly spaced in an array on one side.
8. The method for preparing the piezoelectric flexible super-hydrophobic raindrop sensor according to claim 1, characterized in that: In the step 5, the area of the piezoelectric composite film is smaller than the area of the semi-cured polydimethylsiloxane (PDMS) on the copper template, and the semi-cured polydimethylsiloxane (PDMS) has a microstructure on one side surface, and after covering, the one side surface of the piezoelectric composite film is located at the center position of the other side surface of the semi-cured polydimethylsiloxane (PDMS); the area of the polydimethylsiloxane (PDMS) spin-coated on the other side surface of the piezoelectric composite film is larger than the area of the piezoelectric composite film; the copper template is placed in a culture dish and placed in an oven at 80°C for curing and forming, and then the copper template is taken out.
9. The method for preparing the piezoelectric flexible super-hydrophobic raindrop sensor according to claim 1, characterized in that: In the step 6, the preparation process of the modified nano-titanium dioxide spin-coating liquid is as follows: first, titanium dioxide particles with a particle size of 20 nm and anhydrous ethanol are added to a centrifuge tube at a ratio of 0.01 g / mL, and a micro-oscillator is used to oscillate for 10 minutes, and then the mixture is placed in an ultrasonic cleaning machine at 50°C for ultrasonic treatment and water bath mixing and cleaning for 0.5 hours to obtain a uniform fourth mixed solution; an octadecyltrimethoxysilane TMOS solution is drawn with a pipette and dripped into the fourth mixed solution, and the centrifuge tube is placed in an ultrasonic cleaning machine at 50°C again for ultrasonic treatment and water bath mixing and cleaning for 1 hour, and then the mixture is allowed to stand for 10 minutes to obtain a uniform modified nano-titanium dioxide spin-coating liquid, wherein the volume ratio of the octadecyltrimethoxysilane TMOS solution to the anhydrous ethanol is 1:100; the surface of the piezoelectric composite-super-hydrophobic film is spin-coated with the modified nano-titanium dioxide spin-coating liquid and then placed in an oven for curing at 80°C.
10. A piezoelectric flexible super-hydrophobic raindrop sensor, characterized in that: The piezoelectric flexible super-hydrophobic raindrop sensor is prepared by the method described in any one of claims 1-9.